Acoustic wave and bond rupture based biosensor-- principle and development : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy at Massey University, Palmerston North, New Zealand - Hirst, Evan (Massey University, 2009)
Bond rupture is an experimental methodology that is used to augment a conventional mass balance biosensor. A good point-of-care biosensor is fast, reliable, simple, cost-effective, and detects low concentrations of the target analyte. Biosensor development is a multidisciplinary field and bond rupture testing is of technical interest to many groups. The Bond rupture methodology endows a mass probe with the ability to discern bond strength. The recognition of specific bonds by mass loading is separated from erroneous non-specific binding by a probe of the force between the analyte and the transducer. Bond rupture is achieved by acoustic excitation of the point of attachment. The force is incremented gradually until rupture occurs. The advancement of bond rupture biosensors beyond the lab requires improved understanding of the mechanisms of bond rupture by base excitation, the transducers, and the supporting hardware. Bond rupture has traditionally been used in conjunction with the Quartz Crystal Microbalance (QCM). There exists, however, a variety of sensors and transducers to which the bond rupture methodology could be applied. The time, cost and experience required for comprehensive investigation of all avenues is prohibitive. To further the development of bond rupture characteristic experiments are designed and carried out on the QCM platform. Numerical simulations are constructed which model the current bond rupture approach. This work is limited to the simulation of bond rupture by base excitation. From the results of the experimental investigation a number of improvements to the bond rupture technique are proposed. Improvements are tested by simulation and the Surface Acoustic Wave (SAW) device is selected to advance the bond rupture craft. A prototype SAW bond rupture device is designed. The prototype device is manufactured and tested, confirming the principle of SAW bond rupture. Future work is required to progress the SAW bond rupture methodology before possible integration with other sensor systems. Because of this work, and the evaluation of the SAW bond rupture prototype, much is learned about the advancement of SAW device bond rupture.
Keywords: Surface acoustic wave (SAW); Bond rupture biosensors; Quartz Crystal Microbalance (QCM); Simulation; Fields of Research::290000 Engineering and Technology::291500 Biomedical Engineering